Surgical Excision of Orbital Cysticercosis Lodged in Superior Oblique Muscle. Issue 30 (July 2015) - Ding, Juan; Zhao, Hong; Lin, Jinyong; Mehmet, Borazan.
<x xml:space="preserve">Abstract</x> Abstract Ocular cysticercosis refers to parasitic infections in humans. Most cases were treated by medicine. The case we reviewed was rarely reported with successful surgical intervention treatment. This case report describes a patient with cysticercosis existing in superior oblique tendon. The main symptom of the patient was recurring history of painless orbital swelling and double vision in upgaze. Ocular motility examination revealed a restriction of the right eye in levoelevation. A contrast-enhanced computed tomographic scan of the orbit revealed the presence of a well-defined hypodense cystic lesion within the right superior oblique muscle. The patient was diagnosed with orbital space-occupying mass with acquired Brown syndrome. Surgical exploration of the superior oblique muscle was performed, and the cyst was removed from the eye and confirmed by histopathological examination. After surgery, an ocular motility examination revealed orthotropia in the primary position and downgaze, with mild restriction in levoelevation. Surgical removal could substitute for medical therapy when the cysticercosis is lodged in the superior oblique muscle, although, prior to surgery, important factors, such as patient requirements, surgical skills of the surgeon, and cyst placement, should be considered.